Impact of Leader-Member Exchange on Quitting Intention among Sales Promotion Staff in Surakarta City - Yackie (ID Solutions, 2021)
An organization based on marketing, sales hospitality is one of the spearheads of the company, so human resources play an important role. Valentin (2015) states that human resources are a factor that shows competitive advantage. The purpose of this study was to determine and analyze the effect of LMX, job satisfaction and communication on interest in quitting work based on gender. This research is a descriptive quantitative study with a population of SPB and SPG in the Surakarta City area with 250 respondents as the sample. Data collection was carried out by distributing questionnaires to obtain data about LMX, job satisfaction, communication and interest in quitting work. The results of the analysis conducted show that there is a positive and significant relationship between LMX on job satisfaction, communication and interest in quitting work. From the results of the analysis it is also shown that there is a positive and significant relationship between job satisfaction and communication on the interest in quitting work. Gender differences also have a positive and significant effect in influencing the relationship between work papacy and communication on interest in quitting work.